Improving school results and equity in compulsory education in Sweden - Pareliussen, Jon (OECD Economics Department Working Papers, 2019)
Swedish school results declined for two decades following a series of reforms in the early 1990s decentralising the school system and introducing choice, competition and management by objectives. The general aims and direction of reform were not destined to lower results, but weaknesses of reform design and implementation, against the backdrop of a deep recession, likely contributed to falling outcomes. Residential segregation and the current model of competition and choice increase school segregation and likely reduce equality of opportunity. A coherent set of reforms should strengthen central government institutions, rebuild a regional governance structure and increasingly target funding to pupils' needs. Better steering of competition and school choice implies ensuring that grades fairly represent pupils' skills and knowledge, that municipalities increasingly take the socio-economic mix of pupils into account in entry and investment decisions, and that entry and expansion of private schools are better coordinated to counter school segregation. Teaching needs to become more attractive to raise the quality of recruitment to the profession and to address current and future teacher shortages by improving teacher education, strengthening continuous learning and instigating more cooperation, feedback and support between colleagues. This Working Paper relates to the 2019 OECD Economic Survey of Sweden (http://www.oecd.org/economy/sweden-economic-snapshot/)